The effects of curcumin supplementation added to diet on anthropometric and biochemical status in women with polycystic ovary syndrome: A randomized, placebo-controlled trial - Asan, Sabiha Ataç; Baş, Murat; Eren, Berna; Karaca, Esen (Progress in Nutrition, 2021)
Clinical manifestations of polycystic ovary syndrome (PCOS) include infrequent or absent menses, abdominal obesity, acanthosis nigricans and signs of androgen excess which include acne or seborrhea and insulin resistance. We hypothesized that curcumin added to diet would modulate anthropometric and biochemical status in women with PCOS. This study was performed with the participation of 30 individuals diagnosed with PCOS by physicians. Participants were randomly assigned to curcumin (at a dose of 93.34 mg) or placebo groups. After a period of eight weeks, body weight, body fat mass and waist circumferences (WC) were found lower in the curcumin group than the placebo group (p<0.05). Body weight decreased by 5.8 ± 2.3 kg after intervention in curcumin group (p<0.05) and 3.2 ± 2.5 kg in placebo group (p<0.05). In addition, waist circumferences decreased by 7.2 ± 3.5 cm after intervention in curcumin group (p<0.05) and 4.1 ± 2.1 cm in placebo group (p<0.05). Between-group difference analysis showed that there were significant differences in fasting blood glucose levels, fasting insulin levels, homeostasis model assessment for insulin resistance (HOMA-IR) and C-reactive protein (CRP) levels in curcumin group (p<0.05). On the other hand, between-group difference analysis showed no significant differences in lipid parameters (total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol and triglyceride levels) and hormone levels (p>0.05). These results indicated that curcumin supplementation added to diet in women with PCOS improved the anthropometric measurements and glysemic parameters; however did not restore the hormone and lipid profiles.